Transformation of Lymphocytes in Gonorrhea Before and After Therapy - Esquenazi, Violet (1973)
Patients were studied for lymphocyte transformation responses to a variety of Neisseria gonorrhoeae antigens and to a Neisseria catarrhalis sonicate. Cells from infected patients manifested significant uptake of tritiated thymidine in response to one or more gonococcal antigens. In some cases, deoxyribonucleic acid synthesis was so marked in lymphocytes not challenged by antigens in vitro that added blastogenesis was either obscured or inhibited. At five weeks posttherapy, lymphocytes were relatively nonreactive to gonococcal antigenic stimulation. Blastogenesis in response to N. catarrhalis was also seen for a few gonorrhea patients and normal controls. Cross-antigenicity of catarrhalis organisms and gonococci was indicated by the disappearance of reactivity to catarrhalis sonicate by the lymphocytes of almost all convalescent gonorrhea patients.